(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Cittadinanza e identità religiosa - 2. Cittadinanza e pluralismo religioso - 3. “Cittadinanza integrativa” e libertà religiosa - 4. La Risoluzione 2076 (2015) e la Raccomandazione 2080 (2015). Religious Freedom and Integrative Citizenship. Some Notes on ’Living Together’ in a Plural Society ABSTRACT: Circumcision concerns the religious identity of Jews and Muslims. In addition to these circumcisions which can be defined as "confessional-religious" there are also those related to local customs. These types deserve renewed attention after Resolution 1952 (2013) and Recommendation 2023 (2013) of the Parliamentary Assembly of the Council of Europe, both concerning "the right of children to physical integrity", and subsequent resolutions 2076 (2015) and Recommendation 2080 (2015) devoted to "(R) Religion and Living together in a Democratic Society". Citizenship is, in fact, the much broader horizon to be found behind circumcision. While the first two documents tend to consider non-therapeutic circumcision as a possible assault to the physical integrity of children without, therefore, focusing on the profiles inherent the right to religious freedom and the possible inclusive value of its "recognition" for the purposes of universal citizenship, the latter two, focusing on the freedom of ’living together’ according to the practices of each religion, seem to be more aware of the need to move towards the realization of a European, inclusive and plural citizenship. However, the category of ’living together’, evanescent and ambiguous for its correlation with the principle of majority (as is evident from the most recent case law of the ECHR), requires a new approach that gives it greater objectivity. Concepts such as those of pluralism and plural citizenship, in which civic belonging and religious affiliation can live together, help to go in that direction, renewing, in the end, the membership of a Europe of peoples and not just of economies.